2018
DOI: 10.21307/ane-2018-026
|View full text |Cite
|
Sign up to set email alerts
|

MMP-3 deficiency does not influence the length and number of CA1 dendrites of hippocampus of adult mice

Abstract: Over the past two decades, metalloproteinases (MMPs), including MMP-2, MMP-3, and MMP-9, have been implicated as important players in mechanisms underlying various forms of neuroplasticity. In particular, MMP-3 was found to be involved in both cognitive functions and in plasticity phenomena, but the underlying molecular mechanisms remain largely elusive. In general, it is believed that functional plasticity of neurons is associated with morphological alterations. Interestingly, MMP-9, in addition to playing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In this study, aberrant neuronal morphology was reported in the visual cortex of MMP3-deficient mice [126]. Similar morphological impairments were described in the cerebellum [127] but not in CA1 hippocampal pyramidal cells [128].…”
Section: The Role Of Mmp3 In Ltpsupporting
confidence: 85%
“…In this study, aberrant neuronal morphology was reported in the visual cortex of MMP3-deficient mice [126]. Similar morphological impairments were described in the cerebellum [127] but not in CA1 hippocampal pyramidal cells [128].…”
Section: The Role Of Mmp3 In Ltpsupporting
confidence: 85%
“…However, MMP3 deficiency reduces ECM digestion; therefore, the cognitive enhancement that was observed in the present study cannot be ascribed to extensive ECM cleavage. Although anatomical studies ruled out gross morphological changes in CA1 pyramidal neurons of Mmp3 −/− mice [ 48 ], as well as an impairment in NMDA-dependent excitatory LTP [ 20 ], it cannot be excluded at the present stage that compensatory changes in the genetically modified animals could have contributed to the observed behavioral phenotype in this model.…”
Section: Discussionmentioning
confidence: 99%
“…35 On the contrary, Nowak et al have shown that there are no significant differences between morphology of MMP-3 -/pyramidal neurons in the CA1 hippocampal field in comparison to the wild-type group. 36 Collectively, these studies suggest that the functioning of the MMP-3 in developing CNS is more complex and may depend on the region of the brain.…”
Section: Matrix Metalloproteinase-3 In the Developing Cnsmentioning
confidence: 99%